Analisis Kualitas Website Badan Pusat Statistik Kabupaten Tasikmalaya Menggunakan Metode Usability Testing - Neng Sri Hermawati Sayyidah; Sari Susanti (Jurnal Ilmu Ekonomi, Pendidikan dan Teknik, 2026)
In the rapidly evolving digital era, the presence of websites as a means of information and interaction has become increasingly crucial, especially for public institutions such as Badan Pusat Statistik. Amid the rapid development of technology, government websites play a vital role in promoting transparency and public inclusion. The use of the Organizational Culture Survey platform within Badan Pusat Statistik Tasikmalaya Regency significantly contributes to the internalization of organizational values and the assessment of employee performance. This study aims to evaluate the level of satisfaction with the Organizational Culture Survey website through usability testing, using four variables: learnability, efficiency, memorability, and errors. Data were collected using questionnaires distributed to employees of Badan Pusat Statistik Tasikmalaya Regency, and analyzed quantitatively using SPSS software. The findings of this study provide factual insights into the website’s usability, effectiveness, and areas for development, which can serve as a reference for improving the quality of digital services at Badan Pusat Statistik Tasikmalaya Regency. The analysis shows a correlation value of 0.580 between the independent variables and website satisfaction, indicating a moderately strong relationship. The F-value is recorded at 15.903, with an R Square (R²) of 58%, meaning that 58% of the variation in website satisfaction is explained by the model’s variables, while the remaining 42% is influenced by other factors outside the study. Simultaneously, the variables learnability, efficiency, memorability, and errors have a significant effect on website satisfaction. Partially, only efficiency and memorability have a positive and significant influence, whereas learnability and errors show a negative and significant impact on user satisfaction with the Organizational Culture Survey website at Badan Pusat Statistik Tasikmalaya Regency.